Diet and Nutrition in Pediatric Inflammatory Bowel Diseases - Cucinotta, Ugo (Nutrients, 2021)
Both genetic and environmental factors are involved in the onset of inflammatory bowel disease (IBD). In particular, diet composition is suspected to significantly contribute to IBD risk. In recent years, major interest has raised about the role of nutrition in disease pathogenesis and course, and many studies have shown a clear link between diet composition and intestinal permeability impairment. Moreover, many IBD-related factors, such as poor dietary intake, nutrients loss and drugs interact with nutritional status, thus paving the way for the development of many therapeutic strategies in which nutrition represents the cornerstone, either as first-line therapy or as reversing nutritional deficiencies and malnutrition in IBD patients. Exclusive enteral nutrition (EEN) is the most rigorously supported dietary intervention for the treatment of Crohn’s Disease (CD), but is burdened by a low tolerability, especially in pediatric patients. Promising alternative regimens are represented by Crohn’s Disease Exclusion Diet (CDED), and other elimination diets, whose use is gradually spreading. The aim of the current paper is to provide a comprehensive and updated overview on the latest evidence about the role of nutrition and diet in pediatric IBD, focusing on the different nutritional interventions available for the management of the disease.